Categorization deficiencies and research needs in threatened species: An analysis of the vertebrates and plants of the department of Loreto, Peru - Cossios, E. Daniel (2021)
In order to make decisions on the conservation or management of wild species, it is a priority to know their conservation status. For this purpose, the most widely used method is IUCN’s categorization of species according to the level of threat they face, both globally and nationally. In this article we conducted an analysis of threatened plant and vertebrate species, and of data deficient species in the department of Loreto, the largest and one of the most biodiverse in Peru, to identify the main threats they face, identify information gaps, and compare the national and global lists. According to both lists combined, 226 species considered threatened have been recorded in Loreto. Large differences exist between the national and global lists, mainly for plants and fish. The main threat recorded is habitat loss, which affects most of the threatened terrestrial vertebrate species. Large gaps persist in information on population size and trends for all taxonomic groups, and on distribution for threatened plants. Among the data deficient species, the main gaps are in distribution and population aspects, but also in threats, ecology, and taxonomy. Our results highlight the need to update the list of threatened plants of Peru, as well as to create a list of threatened fish species and to conduct research on the distribution, population, threats, and taxonomy of species with deficient data and threatened species with information gaps.